PENGARUH TINGKAT PEMAHAMAN AGAMA TERHADAP MOTIVASI INVESTASI NASABAH BANK SYARIAH MANDIRI CABANG GORONTALO - Mustofa, Mustofa (El-Qist: Journal of Islamic Economics and Business (JIEB), 2011)
As one who has a high level of religious understanding will always attempt to run the Sharia, consistently. By keeping himself to carry out what God commanded and always trying not to do any act forbidden by God not only in worship studies but also in Fiqh muamalah, i.e. the relationship between fellow human beings—in this case—is the economy. If a muslim wanted to be consistent, then he/she will save his/her money or invest it in the Islamic bank and will not save/invest in interest/usury-based conventional bank. This research aims to study the influence of the level of religious understanding against the customer’s investment motivation in Bank Syariah Mandiri branch in Gorontalo. This research takes three months (August - November 2011), and the location of the research is Bank Syariah Mandiri Syariah branch of Gorontalo. This research uses a quantitative approach, and data analysis is carried out using statistical regression approach with the help of the program SPSS 17.0. The data used are the primary data and secondary data obtained through observation, documentation and questionnaires. The results of this research show that the level of religious understanding—consisting of iman, Islam and ihsan—of Bank Mandiri Syariah customers is relatively high. Investment motivation as well as the customer in the Bank Syariah Mandiri is also high. The statistical calculation based on the results obtained that there was a very significant influence in either partial or shared between the levels of understanding of religion on customer’s investment motivation on Bank Syariah Mandiri